Comparative In vitro and In vivo study of antioxidants and phytochemical content in Bacopa monnieri - Singh2, N. Mohan*, P.S. Jassal1, V. Kumar, R.P. (Recent Research in Science and Technology, 2011)
Medicinal plants are the most important source of life saving drugs for the majority of the worldÃ¢â‚¬â„¢s population. Plant secondaryÃ‚Â metabolitesÃ‚Â areÃ‚Â economicallyÃ‚Â importantÃ‚Â asÃ‚Â drugs,Ã‚Â fragrances,Ã‚Â pigments,Ã‚Â foodÃ‚Â additivesÃ‚Â andÃ‚Â pesticides. Bacopa monnieri L. Penn. commonly known as Ã¢â‚¬Å“BrahmiÃ¢â‚¬Â is an important medicinal herb of the family Scrophulariaceae. It is the foremost brain tonic herb of the Indian System of Medicine and other traditional systems, used primarily as a nerve tonic, to treat insomnia and nervous tension. BacopaÃ¢â‚¬â„¢s antioxidant properties may offer protection from free radical damage in cardiovascular disease and certain types of cancer. Bacopa monnieri showed antibacterial effect on both Gram positive and Gram negative bacteria suggests the passage of active phytochemicals through both the bacterial cell wall. Microropagation is rapid, in vitro clonal multiplication method of elite clones and also helps in dissemination and ex situ conservation of this endangered medicinal plant. The present study is justifiably planned to propagate the valuable medicinal plant Bacopa monnieri L. in in-vitro condition with various combinations/ concentrations of plant growth regulators, and compare the antioxidant and photochemical content difference in the in-vivo and in-vitro cultivated plant of Bacopa monnieri.